SECURITY SISTEM KELISTRIKAN MOTOR INDUSTRI MENGGUNAKAN MEDIA BLUETOOTH BERBASIS MIKROKONTROLER ATMEGA 328 - Al Husain; Fery Sudarto; Chandra Jayusman (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Developments in science and technology have been able to encourage people to address and resolve the problems that exist in everyday life. One of the technologies developed at this time is a microcontroller. Microcontroller is a chip that can perform digital data processing in accordance with a command programming language that so givent currently Microcontroller widely applied in daily life and industry, one for "Electric Motor Industry Security System Using Bluetooth Media-Based Microcontroller ATMEGA 328 "this is a simple tool which can function automatically based on the input of Android phones are sent via Bluetooth to the Microcontroller IC. Microcontroller on this tool aims to control or control the input received and processed, resulting in the output destination of the motor electrical system security industry is to create a tool that can help operate a security system on industrial machinery control panel with automatic phone using Bluetooth media , with so Bluetooth as a liaison between a smartphone with a device that will translate commands sent by a smartphone to be executed Microcontroller.